Discovery of Canagliflozin, a Novel C-Glucoside with Thiophene Ring, as Sodium-Dependent Glucose Cotransporter 2 Inhibitor for the Treatment of Type 2 Diabetes Mellitus - Nomura, Sumihiro; Sakamaki, Shigeki; Hongu, Mitsuya; Kawanishi, Eiji; Koga, Yuichi; Sakamoto, Toshiaki; Yamamoto, Yasuo; Ueta, Kiichiro; Kimata, Hirotaka; Nakayama, Keiko; Tsuda-Tsukimoto, Minoru (Journal of medicinal chemistry, 2010)
We discovered that C-glucosides 4 bearing a heteroaromatic ring formed metabolically more stable inhibitors for sodium-dependent glucose cotransporter 2 (SGLT2) than the O-glucoside, 2 (T-1095). A novel thiophene derivative 4b-3 (canagliflozin) was a highly potent and selective SGLT2 inhibitor and showed pronounced anti-hyperglycemic effects in high-fat diet fed KK (HF-KK) mice.